Diets designed for athletes - Karinch, Maryann (Champaign, IL : Human Kinetics, 2002)
This book tells you what to eat, when to eat it, and why. It gives you sound nutritional advice and the information you need to perform optimally by understanding which supplements will work best for you and your sport.--[book cover]
-- Using performance-enhancing foods -- Eating for energy -- Aiding recovery --Supplementing for strength -- Adding endurance -- Gaining or cutting weight -- Handling extreme conditions -- Fueling to suit your age -- Refueling during competition -- Recharging and replenishing
Includes bibliographical references (pages 214-215) and index
Keywords: Athletes -- Nutrition; Diet